PESAN EDUKASI "BERBAGI PERSPEKTIF" PADA YOUTUBE MENJADI MANUSIA DAN KESADARAN LITERASI KESEHATAN MENTAL KOMUNITAS TEMAN MANUSIA (KTM) - Enrico Yudha Sena, (2021)
Mental health is a mental condition that a person has in good condition, so they can enjoy life and can socialize. Based on the WHO report, mental health problems in Indonesia are the second highest serious problem after heart disease. According to a report from the Indonesian Ministry of Health, during 2020 there were as many as 277,000 mental health cases in Indonesia. In addition, 91% of survivors of mental health disorders did not receive proper treatment and only 9% received proper treatment. The high number of cases and the need for treatment and rehabilitation cannot only depend on medical personnel, but also the responsibility of the whole family to anticipate preventively, so that literacy about mental health is needed for the entire community. Through the data above, it encourages the author to conduct research on the educational message "Sharing Perspectives" on Youtube Menjadi Manusia, on awareness of mental health literacy. This study aims to prove the effect of educational messages on mental health literacy awareness by testing entertainment education theory. An explanatory quantitative approach with survey method was conducted on members of the Teman Manusia Community as the research sample. Sampling was done through purposive sampling. Data was collected through questionnaires distributed through LINE Group to 95 respondents. The results show that the results of the research hypothesis test prove that H0 is rejected and Ha is accepted, so the educational message "Sharing Perspectives" on Youtube Menjadi Manusia has a significant effect on mental health literacy awareness of KTM members.